Does Financial Literacy Matter in Cashless Payment Usage? - Fatih Andesita Wuri Bemby; Alfiyatul Qomariyah (Institute of Research and Community Outreach - Petra Christian University, 2023)
This study aims to examine the effect of social influence and effort expectancy on the intention to use and actual usage of cashless payment systems with financial literacy as moderating variable. To conduct this study questionnaires were distributed to all active accounting students at Airlangga University and from there, 128 research samples were obtained. The collected data were analyzed using WarpPLS 8.0. The results show that effort expectancy and social influence have a positive effect on the intention to use cashless payment systems. The result also shows that the intention to use cashless payment systems has a positive effect on the actual usage of cashless payment systems. In addition, the research results indicate that financial literacy does not moderate the effect of effort expectancy and social influence on the intention to use cashless payment. The results of this study are expected to provide insight and a better understanding of financial literacy and cashless payment system.